Anesthesiologists are like Maestro: A tribute to a Canadian well-wisher - Pradhan, Bishwas (Journal of Society of Anesthesiologists of Nepal, 2016)
This article is a tribute to Clinical Associate Professor Dr Charles Leslie MacAdams from Foothills Hospital, Calgary, Canada